The new dialectic and Marx's Capital - Arthur, C. J. (Christopher John), 1940- (Historical materialism book series, 2004)
This work both argues for, and demonstrates, a new turn to dialectic. Marx's "Capital" was clearly influenced by Hegel's dialectical figures - here, case by case, the significance of these is clarified.